Ethnic Identity in Hanif Kureishi's My Beautiful Laundrette - Kobylková, Kateřina (Univerzita Pardubice, 2019)
This bachelor thesis deals with the analysis of ethnic identity in Hanif Kureishi's play My Beautiful Launderette. In the first chapter of the thesis, the term identity is generally defined. The following chapter is devoted to the analysis of aspects of ethnic identity in individual characters of the aforementioned play. The final chapter covers the living conditions of immigrants and their cohabitation with the mainstream culture depicted in the historical background of the 1980s when Margaret Thatcher presided over the government in the UK.
Etnická identita v díle Hanifa Kureishiho My Beautiful Laundrette
Keywords: identita; etnická identita; Británie osmdesátých let; Moje krásná prádelnička; identity; ethnic identity; 1980s Britain; My Beautiful Launderette